DEVELOPMENT STRATEGY OF RICE COMMODITY TO INCREASE FOOD SECURITY IN THE SOUTH LABUHAN BATU SECURITY TO PUSH NATIONAL ECONOMIC GROWTH - Taufik Hidayah; Faulia Anggeraini; Adetia Azmi Tanjung; Rahmawani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the development strategy of rice commodity agribusiness in improving food security and driving national economic growth in South Labuhanbatu Regency. This research is motivated by the still suboptimal management of rice agribusiness, which is characterized by production fluctuations, limited technology adoption, and the weak bargaining position of farmers in the distribution chain. The study used a mixed method approach involving 17 respondents consisting of farmers, distributors, middlemen, and absorption partners. Data collection was conducted through observation, in-depth interviews, and documentation studies. Data analysis used SWOT analysis, BCG Matrix, SPACE Matrix, and QSPM. The results show that rice agribusiness in South Labuhanbatu Regency is in the Strength–Opportunity position, Star quadrant, and aggressive strategy, which indicates high growth opportunities. The QSPM results indicate that strengthening partnerships between farmers and absorption partners is a priority strategy with the highest appeal. The novelty of this study lies in the integration of four strategic analysis tools in the context of a regional economy based on food security. The research findings provide policy implications that rice agribusiness development needs to be directed at upstream-downstream integration, strengthening farmer institutions, and price stabilization to support food security and national economic growth.